Analysis of the Economic Impact and Life Cycle Costs of Precision Agriculture Implementation in Food Crop Cultivation - Adnan Achmad; Hanisah Hanisah; Silvia Anzitha (International Journal of Management Science and Information Technology, 2026)
To improve the efficiency of agriculture and food crops, the use of modern technology is necessary. Precision Land Management consists of a suite of high-tech tools including sensors, drones, and Geographic Information Systems (GIS) to monitor land and crop conditions in real time. This allows for optimized utilization of inputs such as water, fertilizer, and pesticides. This paper aims to analyze the economic impact of implementing precision agriculture, focusing on its Life Cycle Cost. This includes not only the initial investment, but also current operations, maintenance, and future savings (although there may be some uncertainty regarding the actual costs). This study used Life Cycle Costing (LCC) and Cost-Benefit Analysis (CBA). The results show that the implementation of precision agriculture reduces resource consumption. For example, sensors have reduced water use in West Java by 30%, and variable fertilizer application based on Sumatra has reduced fertilizer consumption by 40%. However, the main obstacle is the high initial investment costs, which are a burden for smallholder farmers. Therefore, policies that support the adoption of precision agriculture technologies through various means such as fiscal incentives and training are urgently needed, and it is also important to ensure that such tools can be freely used by farmers throughout Indonesia.